Forensic Pathology of Society-Oriented Expert Identification Institutions in China: A Retrospective Study by 11-year Data from Academy of Forensic Science - Yuan-Yuan Liu; En-Hao Fu; Ya-Wen Liu; Dong-Hua Zou; Jiang Huang; Hao-Jie Qin; Ning-Guo Liu (Journal of Forensic Science and Medicine)
Objective: The aim of the study was to introduce the development of forensic pathology for social-oriented forensic-identification institutions, using the Academy of Forensic Science as an example. Methods: Cases were collected from the Forensic Pathology Section of the Academy of Forensic Science and classified and organized according to gender, source, type, manner of death, and virtual autopsies of the cases over the years. Descriptive statistical analyses were performed using SPSS and Excel tables so as to summarize forensic pathology for social-oriented services. Results: A total of 12,161 cases were collected from the forensic pathology department; the most cases were from the People’s Public Security sources, and the fewest cases were from the Department of Health; the most cases were commissioned for the examination of cadaver surface in forensic medicine (8323 cases), and the fewest were for injury examination (72 cases) and diatom examination (78 cases); there were a total of 322 cases of virtual autopsy examination during the 11-year period, of which 33 cases were performed for target-organ arteriography; the highest number of cases for accidental death examinations (8122 cases). Conclusion: The Academy of Forensic Science and other social-service-oriented identification organizations undertake identification work on cases commissioned to them by the local and local people’s public security, people’s procuratorates, and people’s court systems. Virtual autopsy technology and other new technologies, new methods, and new standards to make up for the shortcomings of the traditional autopsy, to provide identification and research support, and subsequent prospective research to provide a database.